1998
DOI: 10.1177/009155219802600201
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Instruction, Learning Communities, and Students Studying Together

Abstract: This study was designed to investigate the extent to which peer relations increased among students who participated in a modified program of supplemental instruction at a community college. Peer relations have been examined as a subset of social integration variables in studies of four-year colleges under a variety of labels-contact, interaction, involvement, integration, personal bonds-and with a variety of methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…More specifically, our review revealed that supplemental instruction has been shown to be positively related to student retention, grades, and course completion or success. Moreover, findings by Maxwell (1998) indicate that supplemental instruction may have a positive impact on peer relations. However, it is noteworthy that the ability of the researchers to draw meaningful and useful inferences of all of the supplemental instruction studies may be limited due to selection bias or an absence of experimental designs.…”
Section: Supplemental Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, our review revealed that supplemental instruction has been shown to be positively related to student retention, grades, and course completion or success. Moreover, findings by Maxwell (1998) indicate that supplemental instruction may have a positive impact on peer relations. However, it is noteworthy that the ability of the researchers to draw meaningful and useful inferences of all of the supplemental instruction studies may be limited due to selection bias or an absence of experimental designs.…”
Section: Supplemental Instructionmentioning
confidence: 99%
“…Programmatic efforts for supplemental instruction at community colleges vary as to whether they are required (Marcus, Cobb, & Shoenburg, 1996) or optional conditions of the courses to which they are attached (Zartisky & Toce, 2006). Supplemental instruction programs also vary as to time and length, but they are regularly scheduled and led by either the instructor of the course (Maxwell, 1998) or by student leaders who have already completed the course in question. Students participating in supplemental instruction often work in small groups (Marcus et al, 1996).…”
Section: Supplemental Instructionmentioning
confidence: 99%
“…However, educators who desire to study the persistence of nontraditional students may find that the Tinto's model has limited applicability since it is best suited to institutional analysis of the persistence of traditional undergraduate students (Maxwell, 1998;Rendon, Jalomo, & Nora, 2000). Tinto's model is not as useful for studying the attrition of older students, for whom academic and social integration within the university may be less influential (Bean & Metzner, 1985).…”
Section: Tinto's Student Integration Modelmentioning
confidence: 99%
“…About half of the research studies found a positive relationship between social integration and various outcomes , whereas the other half reported no relationship or even negative correlations (Bers & Smith, 1991 ;Friedlander & MacDougall, 1992 ;Kraemer, 1997 ;Maxwell, 1998 ;Nora, Attinasi, & Matonak, 1990 ;Nora & Rendon, 1990 ;Pascarella, Smart, & Ethington, 1986). This research has led to two conclusion s : (a) The Student Peer Relations 209 frequency of social contact and participation is low among community college students, and (2) the infrequency of relationships among students is uniform or nearly invariant, that is, almost all students similarly have few contacts with each other.…”
mentioning
confidence: 99%